Metrics for aggregating the climate effect of different emissions: A unifying framework - Richard S. J. Tol; Terje K. Berntsen; Brian C. O'Neill; Jan S. Fuglestvedt; Keith P. Shine; Yves Balkanski; Laszlo Makra (The Economic and Social Research Institute (ESRI), 2008)
Multi-gas approaches to climate change policies require a metric establishing equivalences among emissions of various species. Climate scientists and economists have proposed four classes of such metrics and debated their relative merits. We present a unifying framework that clarifies the relationships among them. We show that the Global Warming Potential, used in international law to compare greenhouse gases, is a special case of the Global Damage Potential, assuming (1) a finite time horizon, (2) a zero discount rate, (3) constant atmospheric concentrations, and (4) impacts that are proportional to radiative forcing. We show that the Global Temperature change Potential is a special case of the Global Cost Potential, assuming (1) no induced technological change, and (2) a short-lived capital stock. We also show that the Global Cost Potential is a special case of the Global Damage Potential, assuming (1) zero damages below a threshold and (2) infinite damage after a threshold. The UN Framework Convention on Climate Change uses the Global Warming Potential, a simplified cost-benefit concept, even though the UNFCCC frames climate policy as a cost-effectiveness problem and should therefore use the Global Cost Potential or its simplification, the Global Temperature Potential.
Keywords: 330; climate change; multi-gas climate policy; Global Warming Potential; equivalences between greenhouse gases; Klimaveränderung; Treibhausgas; Umweltbelastung; Umweltschutzkosten; Schätzung; Theorie